A CEMARAN BAKTERI PADA JAJANAN KULINER KUE BASAH DI PASAR TRADISIONAL KOTA MANADO - MICHAEL VALLERY LOUEIS TUMBOL; Angel Fransisca Welua; Agreta Lumenta; Angiela Nofriani; Hana Firlia Suhanda; Praishe Sarajar Allan Andaria; Allan Johannes Andaria (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
The source of microorganism contamination in wet cake snacks can occur in food raw materials, the behavior of sellers and buyers when selling the wet cakes in the market. Cases of bacterial contamination in food often occur and this can cause serious diseases. Based on the above, the problem and purpose of this study is how microbial contamination in wet cake culinary snacks sold in traditional markets in Manado City. Samples of wet cake culinary snacks were taken randomly from six traditional markets in Manado City, then examined in the bacteriology laboratory of the Medical Laboratory Technology Department of the Manado Ministry of Health Polytechnic. The parameters tested were the Total Plate Count (ALT) value and the isolation and identification of Escherichia coli, Staphylococcus aureus and Salmonella sp. bacteria. Based on the results of the study, it can be concluded that bacterial contamination in culinary snacks of wet cakes in traditional markets in Manado City is Escherichia coli contamination of 15 (9.5%) samples, Staphylococcus aureus contamination of 77 (48.7%) samples, Salmonella Sp contamination of 2 (1.3%) samples and contamination identified 2 types of bacteria, namely E. coli and S. aureus of 6 (4.8%) samples. The Total Plate Count (TPC) value of the samples is 76 (48.1%) samples do not meet the requirements and 82 (51.9%) samples meet the requirements.